Connecting organic redox-active building blocks through mild noncatalytic C−H activation - Wild, Ute; Hübner, Olaf; Enders, Markus; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of organic chemistry, 2022)
Compounds with two or more redox-active units, connected by a bridge that supports electronic coupling between the units, have been studied for a long time. Redox reactions could result in mixed-valence compounds, in which the electronic structure depends on the degree of electronic coupling. Here we report the synthesis of the first molecule in which two redox-active guanidines are connected through a bridge. The compound is synthesized in an unprecedented, simple one-step procedure involving an atom-economically favorable, non-catalytic C−H activation reaction at room temperature from novel 1,2,4-trisguanidino-benzene molecules and 1,4-benzenedithiol. We then apply similar protocols to introduce other substituents in 5-position of a 1,2,4-trisguanidino-benzene molecule, demonstrating the scope of these exceptional C−H activation reactions. Finally, we report the synthesis of a hexakisguanidino-biphenyl by direct coupling of two trisguanidino-benzene units through C−H activation. Its oxidation leads to the first mixed-valence compound with charge delocalization between two redox-active guanidino units. The redox states of the resulting novel compounds are systematically studied.